Relationships of on‐farm soil health scores with corn and soybean yield in the midwestern United States. Issue 1 (23rd December 2021) - Crookston, Bradley; Yost, Matt; Bowman, Maria; Veum, Kristen
Abstract: Soil health assessments are interpretive frameworks that estimate a soil's health by scoring various soil biological, chemical, and physical attributes to guide soil and crop management. Few large‐scale analyses of soil health assessment scores exist. Thus, our objectives were to (a) summarize soil health scores at farms across much of the midwestern United States, (b) evaluate how individual soil health indicators influence assessment composite scores, (c) assess correlations among composite scores, and (d) determine the strength of significant correlations between soil health assessment scores and crop yield at three spatial and temporal scales: individual site‐year, individual site, and all sites and years combined. Soil health and yield data were collected from 96 Soil Health Partnership (SHP) farmers across nine midwestern states over 2–5 yr. Soil texture influenced soil health indicator values and scores in the study region. Correlation strengths among the comprehensive assessment of soil health (CASH), the soil management assessment framework (SMAF), and the Haney soil health tool (HSHT) composite scores were soil texture dependent. Multiple years of data at individual sites improved the statistical correlations between yield and soil health scores compared with individual site years. When practitioners judge how well crop yield relates to soil health scores, examining data over time should enhance relationships. These results demonstrate that a multiyear commitment greatly improves soil health monitoring at the site level. Core Ideas: Relationships between scores and yield were analyzed at three spatial and temporal scales. Overall soil health is not best represented by a single indicator for all soil texture groups. Multiple years of data are needed to observe yield–score correlations at an individual site. Patterns in site‐level factors that lead to yield–score correlations were unidentifiable.